2005
DOI: 10.1074/jbc.m502248200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Human Meiosis-specific Recombinase Dmc1 by Ca2+

Abstract: Rad51 and its meiotic homologIn most eukaryotic organisms, meiotic recombination is required for generation of genetic diversity and for accurate segregation of homologous chromosomes (1-3). Mutations that impair meiotic recombination have been reported to increase non-disjunction in Schizosaccharomyces pombe, Saccharomyces cerevisiae, Caenorhabditis elegans, Drosophila, mice, and humans; malfunction of meiotic recombination is a leading cause of trisomies in humans (4).The molecular mechanisms of meiotic reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
104
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(116 citation statements)
references
References 41 publications
12
104
0
Order By: Relevance
“…More recently, a robust Dmc1-mediated strand exchange reaction has been described, which differs from previous studies in using physiological pH and higher salt concentrations 26,[34][35][36] . Under these conditions, helical Dmc1-ssDNA filaments were formed 26,35,37 (Fig.…”
Section: Dmc1-mediated Dna Strand Exchangementioning
confidence: 60%
See 1 more Smart Citation
“…More recently, a robust Dmc1-mediated strand exchange reaction has been described, which differs from previous studies in using physiological pH and higher salt concentrations 26,[34][35][36] . Under these conditions, helical Dmc1-ssDNA filaments were formed 26,35,37 (Fig.…”
Section: Dmc1-mediated Dna Strand Exchangementioning
confidence: 60%
“…Ca 2+ stimulates both filament formation on ssDNA and DNA strand exchange by bacterially expressed human and yeast Dmc1 proteins 35,36 . Ca 2+ also stimulates Rad51 (ref 39), so it has been suggested that Dmc1 and Rad51 activity might be modulated in vivo by variation in intracellular calcium levels 35,36 .…”
Section: Dmc1-mediated Dna Strand Exchangementioning
confidence: 99%
“…In the case of RAD51, Ca 2ϩ maintains an active presynaptic filament by blocking ATP hydrolysis and thereby preventing the self-inhibition that accompanies accumulation of ADP within the filament. In contrast, for DMC1, Ca 2ϩ does block ATP hydrolysis, but this is not the basis for stimulation because a similar stimulation by Ca 2ϩ is observed in the presence of the non-hydrolyzable AMP-PNP; thus, Ca 2ϩ apparently induces a conformational change in the filament assembled on ssDNA that enables more effective DNA strand exchange (35,42). For yeast Dmc1, the modulation by Ca 2ϩ is similar to human DMC1 in that Ca 2ϩ also stimulates joint molecule formation slightly when AMP-PNP is used (supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1C) established that the protein binds ssDNA. Previous reports established that yeast, as well as human, Dmc1 forms stable filaments only in the presence of calcium (34,35). We therefore examined the ability of Dmc1 to form complexes with ssDNA in the presence of magnesium acetate or calcium acetate (henceforth referred to as Mg 2ϩ and Ca 2ϩ , respectively).…”
Section: Purified Recombinant Dmc1 and Tid1 Proteins Are Activementioning
confidence: 99%
“…However, subsequent studies showed that, under certain conditions, Dmc1 forms right-handed filaments similar to those formed by the other recombinases (Sehorn et al 2004;Burgreev et al 2005;Lee et al 2005). Interestingly, substitution of Mg 2+ with Ca 2+ resulted in formation of long helical filaments on single-stranded DNA (ssDNA); Ca 2+ stimulated Dmc1's strand assimilation and strand exchange activity as well (Bugreev et al 2005;Lee et al 2005). Although it remains to be seen if Ca 2+ is a biologically relevant modifier of Dmc1 activity, it is clear that conditions favoring filament formation enhance recombinase activity.…”
mentioning
confidence: 99%